Direct Design of Controllers Using Complementary State and State-Derivative Feedback - Rossi, Fernanda Quelho; Galvão, Roberto Kawakami Harrop; Teixeira, Marcelo Carvalho Minhoto [UNESP]; Assunção, Edvaldo [UNESP] (Springer Nature, 2019)
This paper is concerned with controllers design using complementary state and state-derivative feedback, as an extension of the work presented in Rossi et al. (in: Proceedings of XXI Congresso Brasileiro de Automática, Vitória, Brazil, pp 828–833, 2016). The novel approach is more general, in that it enables the direct design of an CSSDF controller, dispensing with the need for a preliminary state feedback design. For this purpose, a discrete-time design model is derived to describe the plant dynamics in terms of the state and state-derivative combinations available for feedback. The resulting model can be used with existing discrete-time state-space methods for the design of linear or nonlinear control laws. Simulation examples are presented to illustrate the proposed design method within a model predictive control formulation.
Keywords: Complementary state and state-derivative feedback; Direct design; Discrete time; Model predictive control